SHARIAH ECONOMIC LAW IN A GLOBALIZED MARKET: LEGAL ADAPTATION, HARMONIZATION, AND RESISTANCE - Zeynep Toprak; Cemil Kaya; Eva Janssen (Yayasan Adra Karima Hubbi, 2026)
Shariah economic law is increasingly shaped by the dynamics of globalization, where cross-border finance, international standards, and regulatory convergence influence how Islamic legal principles are interpreted and applied. Expanding integration into global markets raises critical questions about the balance between legal adaptation, harmonization, and resistance, particularly in maintaining normative integrity while ensuring economic competitiveness. This study aims to examine how these three legal orientations interact in shaping contemporary Islamic economic law across different jurisdictions. A qualitative normative–juridical research design is employed through systematic analysis of 98 legal documents, including jurisprudential texts, regulatory frameworks, and international standards. Analytical matrices and thematic coding are used to identify patterns of legal transformation, institutional mediation, and interpretive diversity. The findings reveal that Shariah economic law evolves through a dynamic interplay of adaptation, harmonization, and resistance, with hybrid frameworks emerging as dominant responses to global pressures. Harmonization enhances regulatory coherence, adaptation ensures contextual flexibility, and resistance preserves doctrinal authenticity. The study concludes that effective governance requires integrative approaches that balance global alignment with normative preservation, ensuring that Islamic economic law remains both relevant and ethically grounded in a globalized financial system.